2019
DOI: 10.1021/acs.chemrestox.9b00168
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Mono-Triazole Derivatives Inhibit Aβ42 Aggregation and Cu2+-Mediated Aβ42 Aggregation and Protect Against Aβ42-Induced Cytotoxicity

Abstract: Amyloid beta (Aβ) peptide aggregation is considered as one of the key hallmarks of Alzheimer’s disease (AD). Moreover, Aβ peptide aggregation increases considerably in the presence of metal ions and triggers the generation of reactive oxygen species (ROS), which ultimately leads to oxidative stress and neuronal damage. Based on the ‘multitarget-directed ligands’ (MTDLs) strategy, we designed, synthesized, and evaluated a novel series of triazole-based compounds for AD treatment via experimental and computation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 112 publications
0
19
0
Order By: Relevance
“…It has been shown by several researchers that the interaction of Cu(II) with peptides and proteins leads to ROS formation [ 44 , 45 , 56 , 60 , 61 ]. Therefore, the Aβ-Cu(II) system can be used as an oxidative stress inducer in the SH-SY5Y in vitro model to mimic the AD-like oxidative stress condition [ 62 , 63 ]. Among the Aβ isoforms, Aβ 1–42 is more hydrophobic and fibrillogenic than Aβ 1–40 due to the addition of two hydrophobic residues at the N-terminus [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown by several researchers that the interaction of Cu(II) with peptides and proteins leads to ROS formation [ 44 , 45 , 56 , 60 , 61 ]. Therefore, the Aβ-Cu(II) system can be used as an oxidative stress inducer in the SH-SY5Y in vitro model to mimic the AD-like oxidative stress condition [ 62 , 63 ]. Among the Aβ isoforms, Aβ 1–42 is more hydrophobic and fibrillogenic than Aβ 1–40 due to the addition of two hydrophobic residues at the N-terminus [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Until now, an effective treatment for AD does not yet exist. It is crucial to find effective inhibitors for the treatment of AD. A large number of experimental studies reported that several different types of potential inhibitors, including nanoparticles, , short peptides, small molecules, , multitarget-directed ligands, and antibodies, , are able to dissociate Aβ fibrils and/or inhibit Aβ aggregation. Inspired by those experimental studies, several computational groups investigated the inhibitory mechanisms using MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the cell survival rate increased to 73.7% and 90.5%, respectively, when the concentrations of alizarin/purpurin were 200 μM. Therefore, it was concluded that alizarin and purpurin had a significant inhibitory effect on insulin aggregates-induced cytotoxicity, which was attributed to their effective inhibition of insulin aggregation. , …”
Section: Results and Discussionmentioning
confidence: 91%
“…Therefore, it was concluded that alizarin and purpurin had a significant inhibitory effect on insulin aggregates-induced cytotoxicity, which was attributed to their effective inhibition of insulin aggregation. 40,41 Effects of Alizarin/Purpurin on Insulin Amyloid Defibrillation. In addition to the inhibition ability of alizarin/purpurin on the formation of amyloid fibrils, whether the two anthraquinone compounds could destroy and clear the preformed insulin fibrils was unknown.…”
Section: ■ Results and Discussionmentioning
confidence: 99%